HUBUNGAN ANTARA INTENSITAS PENGGUNAAN GAME ONLINE MOBILE LEGENDS TERHADAP PERILAKU PROKRASTINASI AKADEMIK PADA SISWA SMA N 11 MUARO JAMBI - Lita Amelia; Rasimin Rasimin; Freddi Sarman (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Given the general and specific problems that arise, a large number of students still prefer to spend their time playing games rather than working on what they are supposed to do so academic procrastination is very frequent. This happens because of the increasingly sophisticated times and all things can be accessed easily through mobile phones, one of which is to play online games. This study aims to reveal the intensity of mobile legends online game use and academic procrastination behavior in students of SMA N 11 Muaro Jambi. The study was limited to academic procrastination behaviors including delaying starting or completing tasks on time, starting or completing tasks later than planned, and engaging in other, more enjoyable activities. The sample in this study was 104 students of SMA N 11 Muaro Jambi consisting of classes X and XI. Likert scale questionnaires with multiple choice answers for two variables were used in this study. To ensure the relationship between the independent variable (X) and the dependent variable (Y), correlation research was conducted using a quantitative approach using the product moment method. This study shows a positive correlation between academic procrastination behavior and the level of mobile legends online game usage. The correlation analysis processing value of 0.589 falls into the moderate or adequate relationship category In addition, the percentage of students who use the mobile legends online game intensely (60%) falls into the High category, while the percentage of students who procrastinate on their academic work (38%) falls into the Low category. Therefore, students at SMA N 11 Muaro Jambi show less academic procrastination behavior and the less they use mobile legends online games